Quantitative analysis of social media use in the energy and resources sector: national comparison and sector analysis - Duojie, Caidan; Liu, Shiyu (Frontiers in Ecology and Evolution, 2023)
Herein, we analyzed the adoption and use of various social media platforms by companies operating in the energy and resources sector of five countries: India, China, Japan, the United States of America (USA), and Russia, using survey checklists and linear regression analysis. All companies maintained a strong online presence through corporate websites, email contacts, and various social media platforms. However, the adoption and use of social media platforms differed for each country; for example, firms from India, the USA, and Russia had a stronger social media presence than firms in China and Japan. According to the sector analysis, corporate blogs had the highest usage rate (77%), followed by LinkedIn and Facebook (58% and 53%, respectively). The number of enterprises adopting new social media platforms was highest in 2014 (14.1%). Linear regression analysis revealed that companies should constantly update their relevant information on Facebook, Twitter, Instagram, and LinkedIn and increase the total views of YouTube channels to increase their followers, improve their influence and popularity, and achieve better interaction with stakeholders. In conclusion, the global energy and resources sector has made strategic efforts toward maintaining a strong online presence by operating official corporate websites and maintaining an active social media presence.